1985
DOI: 10.1113/jphysiol.1985.sp015738
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a sympatho‐inhibitory and vasodilator reflex evoked by superior laryngeal nerve afferents in the cat.

Abstract: SUMMARY1. The background discharge of sympathetic preganglionic neurones shows a marked inspiration-synchronous component which is known to originate from within the central nervous system. The contribution of this component to total neurogenic vasoconstrictor tone is unknown.2. In order to estimate its extent we have exploited the inspiration-suppressing effect of a group of low threshold afferent fibres in the superior laryngeal nerve.3. The electrical activities of the cervical sympathetic trunk and of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…These findings suggest that the vasodilation elicited by ES of the ADN may be initiated by the withdrawal of sympathetic neurogenic vasoconstrictor drive, rather than the release of newly synthesized NOFs. Moreover, these findings suggest that the hindlimb vasodilation initiated by ES of the SLN may be due to activation of nonbaroreceptor afferents in this nerve (4,16,19,31). However, the total hindlimb vasodilation in response to ES of the ADN was substantially reduced by 7-NI.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These findings suggest that the vasodilation elicited by ES of the ADN may be initiated by the withdrawal of sympathetic neurogenic vasoconstrictor drive, rather than the release of newly synthesized NOFs. Moreover, these findings suggest that the hindlimb vasodilation initiated by ES of the SLN may be due to activation of nonbaroreceptor afferents in this nerve (4,16,19,31). However, the total hindlimb vasodilation in response to ES of the ADN was substantially reduced by 7-NI.…”
Section: Discussionmentioning
confidence: 92%
“…The hindquarter vasodilation is largely dependent on the integrity of the lumbar sympathetic chain (16,31) and may involve the release of NOFs from NOS-positive sympathetic nerve terminals (31). The SLN contains mechanosensitive, chemosensitive, and baroreceptor afferent fibers (4,16,19,31). Therefore, it was not possible to determine which afferent fiber type within the SLN may have been responsible for the activation of the lumbar sympathetic vasodilator system (31).…”
mentioning
confidence: 98%
“…Oscillations in the sympathetic outflow are modulated by the respiratory rhythm in rats (Numao et al, 1987;Haselton and Guyenet, 1989) and humans (Badra et al, 2001;Dempsey et al, 2002), and this modulation contributes to the neurogenic vasomotor tone (Bachoo and Polosa, 1985). This phenomenon is in part a consequence of activation of pulmonary stretch receptors (Zhou et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Bachoo & Polosa (1985) have recently shown that the discharge ofinspiratory-related sympathetic preganglionic neurones maybeimportant in determining vasoconstrictor tone and sympathetic drive to the heart. This proposal is supported by the observation that sympathetic activity in inferior cardiac nerve fibres, renal nerve fibres and skeletal muscle vasoconstrictor fibres supplying the hind limb of the cat (Gregor, Janig & Wilprich, 1977;Bainton et al 1985; M. P. Gilbey, A. G. Ramage & L. M. Wood, unpublished observations) displays a strong inspiratory synchronous discharge.…”
Section: Functional Implicationsmentioning
confidence: 99%